RANCANG BANGUN SISTEM INFORMASI PELANGGARAN DAN PERMASALAHAN SISWA DI SEKOLAH - Arif Budiman; Alhamidi; Rini Asmara (SAINS DAN INFORMATIKA : RESEARCH OF SCIENCE AND INFORMATIC, 2021)
In the activities of the learning process at school sometimes there are many violations that are often committed by school students. In addition to violations, there are also problems that often involve students as perpetrators. With an application designed for data processing of student problems and violations based on SMS Gateway, where the new system is a development of the old information system. It is hoped that the new system that the author designed can replace the old system, in order to achieve a higher level of effectiveness and efficiency. In designing this application using the waterfall method which can help produce good applications so that the design can produce applications that are used by schools to obtain information on student problems and violations. With the implementation of this application, it can help schools to find out all the problems faced by students so that they can provide the right solution. And this application is also very helpful for schools to make quick decisions, even parents of students also get information on points of violations that have been committed by students via SMS Gateway.